The prevalence and distribution of aminoglycoside resistance genes - Yuan Zhang; Ning Zhang; Mengyu Wang; Ming Luo; Yao Peng; Zhenpeng Li; Jialiang Xu; Meiling Ou; Biao Kan; Xu Li; Xin Lu (Elsevier, 2023)
Choosing the appropriate antibiotics to treat bacterial infections has grown more challenging as a result of the emergence of antibiotic-resistant bacteria. Aminoglycosides, as broad-spectrum antibiotics, are increasingly being used clinically; however, for most effective employment of aminoglycosides, a comprehensive understanding of aminoglycoside resistance genes' prevalence and dissemination is required. Therefore, to better understand the global resistance status of aminoglycoside antibiotics and the prevalence of antibiotic-resistance genes (ARGs) in various bacterial species, this systematic review gathered relevant data from multiple studies. Two primary resistance mechanisms-aminoglycoside enzymatic modification and 16S rRNA methylation-were assessed, and the prevalence of the corresponding ARGs was described. The coexistence of aminoglycoside ARGs with other ARGs was also demonstrated, as was the relationship between aminoglycoside ARGs and resistant phenotypes. The lack of effective therapeutic agents to combat resistant pathogens presents a real threat to public health. The combination of aminoglycosides with other antibiotics may provide a novel treatment strategy.